2020
DOI: 10.1371/journal.pone.0239164
|View full text |Cite
|
Sign up to set email alerts
|

The association between transition from metabolically healthy obesity to metabolic syndrome, and incidence of cardiovascular disease: Tehran lipid and glucose study

Abstract: Considering that the data available on the cardiovascular (CV) risk of metabolically healthy obesity phenotype, and the effect of transition to an unhealthy status are inconsistent, the aim of this study was to investigate the possible role of transition to unhealthy status among metabolically healthy overweight/obese (MHO) subjects on CVD incidence over a median follow-up of 15.9 years. In this large population-based cohort, 6758 participants (41.6% men) aged � 20 years, were enrolled. Participants were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
18
1
3
Order By: Relevance
“…MHO/OW incidence in this study was similar previous studies [4,8,30,31]. The recent Hosseinpanah cohort study showed that 26.9% of male and 39.4% of female Iranian people were MHO [31].…”
Section: Discussionsupporting
confidence: 91%
“…MHO/OW incidence in this study was similar previous studies [4,8,30,31]. The recent Hosseinpanah cohort study showed that 26.9% of male and 39.4% of female Iranian people were MHO [31].…”
Section: Discussionsupporting
confidence: 91%
“…In a recent Iranian study, neither women nor men with persistent MHO status had increased HR for CVD incidence compared to the non-obese comparison group (35). However, among women and men who transitioned from MHO to MUO, only men had an increased HR compared to the non-obese comparison group (35). In the study by Izumida et al, the authors adjusted for sex, whereas we found an interaction, but only regarding CVD mortality.…”
Section: Discussioncontrasting
confidence: 79%
“…However, the meta-analysis included few sex-strati ed studies. In a recent Iranian study, neither women nor men with persistent MHO status had increased HR for CVD incidence compared to the non-obese comparison group (35). However, among women and men who transitioned from MHO to MUO, only men had an increased HR compared to the non-obese comparison group (35).…”
Section: Discussionmentioning
confidence: 89%
“…However, the meta-analysis included few sex-stratified studies. In a recent Iranian study, neither women nor men with persistent MHO status had increased HR for CVD incidence compared to the non-obese comparison group [ 32 ]. However, among women and men who transitioned from MHO to MUO, only men had an increased HR compared to the non-obese comparison group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Iranian study, neither women nor men with persistent MHO status had increased HR for CVD incidence compared to the non-obese comparison group [ 32 ]. However, among women and men who transitioned from MHO to MUO, only men had an increased HR compared to the non-obese comparison group [ 32 ]. In the study by Izumida et al, the authors adjusted for sex, whereas we found an interaction, but only regarding CVD mortality.…”
Section: Discussionmentioning
confidence: 99%